Caracterização petrográfica e química de clorita e mica branca do depósito aurífero do Basílio, Província de Alta Floresta (MT) - Silva, Felipe Lucio da [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The Alta Floresta Gold Province (AFGP), located at north of Mato Grosso State, hosts more than a hundred medium- to high-grade and low tonnage gold-rich deposits. The province is placed at the southernmost portion of the Amazon Craton, where the gold deposits are concentrated along the NW-SE Peru-Trairão belt. Its mineralizations are hosted in Paleoproterozoic plutonic, volcanic and volcano-sedimentary sequences. Into this context, the primary gold deposits can be grouped into the following groups: (1) disseminated Au ± Cu deposits; (2) vein-type Au ± Cu deposits; (3) disseminated Cu + Mo ± Au deposits; and (4) vein-type Au + Pb + Zn ± Au deposits. In common, these deposits share the metalogeny controlled by magmatic-hydrothermal systems similar to Au-porphyry and low- to intermediate sulfidation epithermal systems. Although the major geological features of these deposits are known, mineral chemistry studies are scarce mainly if considered the hydrothermal halos compositions related to the mineralized zones. The chemical analysis of the typical-ocurring minerals from these halos, mainly represented by white mica (phyllic alteration) and chlorite (propylitic and chlroritic alterations) can provide further information about their mineral-forming processes, such as pressure and temperature. This work, therefore, goals the petrographic and chemistry characterizations of the chlorite and white mica from the vein-type Au ± Cu Basílio deposit (group II). Thus, four textural varieties of chlorite (pseudomorphic, venular, anomalous birefringence and intersticial) and four of white mica (lamellar sericite, pseudomorphic sericite, intersticial sericite and subhedral muscovite) were characterized. The chlorite is, generally, characterized as brunsvigite, where the anomalous birrefringence variety is Mg-enriched, while the others, Fe-enriched. The white mica, on the other hand, shows a wide compositional variation, from muscovite-like compositions...

A Província Aurífera de Alta Floresta (PAAF), localizada no norte do Estado de Mato Grosso, é reconhecida por conter mais de uma centena de depósitos auríferos de médio a alto teor e pequena tonelagem. A Província insere-se no arcabouço sul do Cráton Amazônico, região em que os depósitos estão distribuídos ao longo do lineamento estrutural NW-SE do Peru- Trairão. Suas mineralizações ocorrem hospedadas em sequências plutônicas, vulcânicas e vulcanossedimentares paleoproterozoicas. Nesse cenário, são reconhecidos quatro grupos de depósitos auríferos: (1) Au ± Cu disseminado; (2) Au ± Cu estruturalmente controladas; (3) Cu + Mo ± Au disseminado e (4) veios de Au + Pb + Zn ± Au. Possuem em comum, a metalogênese controlada por sistemas magmático-hidrotermais semelhantes aos dos tipos Au ± Cu pórfiro e epitermal tipo low e intermediate sulfidation. Nesse contexto, ainda que existam estudos avançados na caracterização metalogenética dos principais depósitos localizados na região leste da província, pouco fora produzido em relação à caracterização química dos halos hidrotermais que envolvem as zonas mineralizadas dos depósitos. A análise química de minerais característicos desses halos hidrotermais, na PAAF representados principalmente por mica branca (alteração fílica) e clorita (alterações propilítica e clorítica), pode fornecer importantes informações quanto às condições de P-T sob as quais foram formados. Esse trabalho, portanto, objetiva a caracterização petrográfica e química da clorita e mica branca do depósito de Au ± Cu filonar (grupo II) do Basílio. No depósito, foram caracterizadas quatro variedades texturais de clorita (pseudomórfica, venular, birrefringência anômala e intersticial) e quatro de mica branca (sericita lamelar, sericita pseudomórfica, sericita intersticial e muscovita subedeudral). A clorita, em geral, é caracterizada como brunsvigita, com a variedade de...
Keywords: Petrologia; Geoquímica; Mica; Ouro; Mineralogia; Alta Floresta (MT)